PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL INTERVENING PADA PDAM KOTA SOLOK - Annalisa Saputri; Selvi Yona Sari; Yosi Puspita Sari (Yayasan Tri Edukasi Ilmiah, 2024)
This study aims to determine how much influence competence and compensation have on employee performance through organizational citizenship behavior as an intervening variable. In this study, the object used is PDAM Kota Solok. The data collection method is through primary data and the data collection technique is through a questionnaire. This research uses 83 samples of respondents who are permanent employees. The research data analysis can be calculated through descriptive statistical analysis and multiple linear regression analysis. Based on the research results obtained from the Partial Test (t test) obtained: Competence has a significant effect on Organizational Citizenship Behavior, Compensation has a significant effect on Organizational Citizenship Behavior, Competence has a significant effect on employee performance, Compensation has a significant effect on employee performance, Organizational Citizenship Behavior has a significant effect on employee performance. Competence has no significant effect on organizational citizenship behavior through employee performance. Compensation has no significant effect on organizational citizenship behavior through employee performance.